An analysis of organisational factors related to affective organisational commitment of Secondary school teachers in Mashonaland Central Province of Zimbabwe - Kasowe, Rittah (IJRDO- Journal of Educational Research, 2017)
Performance of secondary school pupils accelerated in a declining manner since 1984 to date.Although much has been done to improve conditions of the teacher since the teachers are at thehelm of students learning, students’ performance has continued to decline. Despite trainingobtained from teachers colleges, what is contributing to their effectiveness has not been wellresearched. Affective organisational commitment of secondary school teachers in Zimbabwestill remain an inadequately researched area. Whereas teachers could be motivated byemployers, the gendered outcomes of their commitment to the organisation especially on theiraffective commitment has not been adequately investigated. The primary purpose of the studywas to make a critical analysis of variables and factors contributing to affective organisationalcommitment using Stufflebeam (2007)’s Context Input Process and Product decisionfacilitation model of evaluation approach. The approach specified the imbalances in each phaseof evaluation focusing on, organisational factors, how each factor contributed to affectiveorganisational commitment of secondary school teachers. The study used statistical tests ofmultiple regression analysis and step wise regression analysis on quantitative survey dataobtained from Affective organisational commitment. The quantitative data were gathered usingtwo seven point Likert scales ranging from strongly agree to strongly disagree. A statisticalprogram SPSS was used to investigate the relationships among variables in the research model.Regardless of the types of dependent or independent variables, linear multiple step wiseregression analyses were performed in order to find out the significance of the variables. Thiswas supplemented by qualitative data gathered and addressing organisational factors. Thequalitative data were collected using semi structured face to face interviews and focus groupdiscussions in order to triangulate the evidence obtained from quantitative data. The qualitativedata were analysed using NVIVO to come up with themes. Thus this study used a mixedmethodology approach. The study established that factors such as; occupational status,management worker relationship, recognition, variety in the profession, opportunity to useability and subject specialisation, were strong determinants of affective organisationalcommitment related to secondary teachers’ affective organisational commitment and impactingnegatively on pupils’ and schools’ performance. The study recommended that Educationalplanners must involve teachers in policy decision making at all levels, provide support and staffdevelopment workshops. Future researchers might wish to expand on studies that indicate aconnection between factors established and the degree of pupils’ performance.